Gender-Based Comparative Study Of The Influence Of Cola Nitida On The Sweat Sodium, Potassium And Chloride Concentrations Of Humans - Igbinovia Igbinovia; Edokpolor Nestor; Ohiwerei Wisdom Omogbai; Ibhadode Adesua; Festus, Oloruntoba O.; Echekwube Marylyn E (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The study investigated how Cola nitida affects the sweat concentrations of sodium (Na), potassium (K), and chloride (Cl) in male and female subjects. Sixty healthy participants (30 males, 30 females) aged 18–28 years, with varying body weights (underweight, normal weight, overweight), were selected. Subjects were exposed to three conditions: normal chamber temperature (27°C, 70% RH), raised temperature (37°C, 90% RH), and exercise at normal temperature (27°C, 70% RH) while riding a bicycle ergometer at 750J/min for 20 minutes. Prior to the experiment, 0.5g/kg body weight of Cola nitida was consumed, followed by a 90-minute rest. Sweat samples were collected to measure ion concentrations. Results showed no significant changes in sodium (Na) concentrations between males and females under normal and raised temperature conditions. However, under exercise conditions, there was a significant increase in sweat Na in female underweight subjects compared to males. Regarding chloride (Cl), there was no significant difference between males and females under all conditions. For potassium (K), significant increases were observed in the sweat of female underweight subjects compared to males in normal, raised temperature, and exercise conditions. Conversely, decreases in sweat potassium were noted in female normal weight subjects under normal conditions and overweight subjects under raised temperature and exercise conditions compared to males.